Pregnancy and neonatal outcome with maternal exposure to finasteride: Case series - Hessah F BinJadeed; Abdulmajeed Alajlan (Wolters Kluwer Medknow Publications, 2021)
Background: Finasteride, a type II 5-α reductase inhibitor, is approved for the management of benign prostate hyperplasia and male pattern hair loss. Finasteride is used off-label for female pattern hair loss. In utero fetal exposure to finasteride might lead to external genital anomalies in males. Purpose: The aim of this study is to assess the outcomes of in utero finasteride exposure. Methods: We report seven pregnant women with maternal exposure to finasteride. A detailed history was obtained from patients after delivery. Results: In one woman who was pregnant with twin boys, one boy died at the 16th week of gestation and the other delivered at the 34th week of gestation with hypospadias. Another woman had threatened abortion and delivered a normal healthy baby girl. A third had induced elective abortion in the 9th week of gestation. The outcomes of the other four pregnancies were completely healthy, three girls and one boy. Conclusion: External genital anomalies may occur in male fetuses exposed in utero to finasteride depending on the timing of exposure.